Mare stromal endometrial cells differentially modulate inflammation depending on oestrus cycle status: an in vitro study - Wong, Yat S.; Mançanares, Ana C.; Navarrete, Felipe I.; Poblete, Pamela M.; Méndez-Pérez, Lídice; Ferreira-Dias, Graça M. L.; Rodriguez-Alvarez, Lleretny; Castro, Fidel Ovidio (Frontiers in Veterinary Science, 2023)
The modulation of inflammation is pivotal for uterine homeostasis. Here we evaluated the effect of the oestrus cycle on the expression of pro-inflammatory and anti-inflammatory markers in a cellular model of induced fibrosis. Mare endometrial stromal cells isolated from follicular or mid‐luteal phase were primed with 10 ng/mL of TGFβ alone or in combination with either IL1β, IL6 or TNFα (10 ng/mL each) or all together for 24 hours. Control cells were not primed. Messenger and miRNA expression were analysed using real time quantitative PCR (RT-qPCR). Cells in the follicular phase primed with pro-inflammatory cytokines showed higher expression of collagen-related genes (CTGF, COL1A1, COL3A1 and TIMP1) and mesenchymal marker (SLUG, VIM, CDH2 and CDH11) genes; p<0.05. Cells primed during the mid-luteal overexpressed genes associated with extracellular matrix, processing and prostaglandin E synthase (MMP2, MMP9, PGR, TIMP2 and PTGES; p<0.05). There was a notable upregulation of pro-fibrotic miRNAs (miR17, miR21 and miR433) in the follicular phase when the cells were exposed to TGFβ + IL1β, TGFβ + IL6 or TGFβ + IL1β + IL6 +TNFα. Conversely, in cells from the mid‐luteal phase, the treatments either did not or diminished the expression of the same miRNAs. On the contrary, the anti-fibrotic miRNAs (miR26a, miR29b, miR29c, miR145, miR378 and mir488) were not upregulated with treatments in the follicular phase. Rather, they were overexpressed in cells from the mid-luteal phase, with the highest regulation observed in TGFβ + IL1β + IL6 + TNFα treatment groups. These miRNAs were also analysed in the extracellular vesicles secreted by the cells. A similar trend as seen with cellular miRNAs was noted, where anti-fibrotic miRNAs were downregulated in the follicular phase, while notably elevated pro-fibrotic miRNAs were observed in extracellular vesicles originating from the follicular phase. Pro‐inflammatory cytokines may amplify the TGFβ signal in the follicular phase resulting in significant upregulation of extracellular matrix-related genes, an imbalance in the metalloproteinases, downregulation of estrogen receptors and upregulation of pro-fibrotic factors. Conversely, in the luteal phase, there is a protective role mediated primarily through an increase in anti-fibrotic miRNAs, decrease in SMAD2 phosphorylation, and reduced expression of fibrosis-related genes.